Uncertainty concepts for integrated modeling - Review and application for identifying uncertainties and uncertainty propagation pathways. (January 2021) - Kirchner, Mathias; Mitter, Hermine; Schneider, Uwe A.; Sommer, Mark; Falkner, Katharina; Schmid, Erwin
Abstract: We review concepts that have been used to address uncertainty in integrated modeling. Although conceptual approaches to tackle uncertainty seem diverse, a synthesis reveals more similarities than differences in the concepts published, especially if one adopts a model application-oriented focus. Given our findings, we slightly adapt the uncertainty framework table (UFT) developed by Walker et al. (2003) and apply it for an existing integrated modeling framework for the bio-economy. The use of color coded UFTs with a graphical visualization of uncertainty propagation pathways has facilitated a better overview and communication of uncertainties and uncertainty propagation pathways among the authors. Systematic consideration of uncertainties in integrated modeling may allow for more trust in model results and, if simulations are conducted, for a better robustness check of policy interventions. Highlights: We review uncertainty concepts for integrated modeling. Focus is put on eliciting uncertainties and uncertainty propagation pathways. An adapted uncertainty concept is applied for an integrated modeling framework. The adapted uncertainty concept helps to identify relevant uncertainties. Further application of the uncertainty concept to test its usefulness is warranted.